Sistem Pengembangan Chatbot Whtasapp Untuk Monitoring Hasil Pembelajaran Siswa Di SMK Negeri 3 Kuningan Menggunakan Metode Waterfall - Zaenal Abidin, Zihan; Muhidin, Asep; Danny, Muhtajuddin (Teknik Informatika, Universitas Pelita Bangsa, 2023)
Service is an activity or sequence that occurs in direct interaction between individuals and others or machines physically, providing customer satisfaction. In the service or information access at SMK Negeri 3 Kuningan, conventional methods are still used, requiring time to access them. For example, when students need to inquire about grades in specific subjects, they have to meet the respective teachers. Therefore, to address this issue, a chatbot solution is developed as a platform to facilitate information retrieval. The development of this chatbot utilizes the waterfall method, which involves several stages including needs analysis, system design, program coding, system testing, and maintenance. The testing in this research adopts the black box testing method. This study results in a chatbot for monitoring student learning at SMK Negeri 3 Kuningan, which assists students in accessing the required information. Keywords: Service, Chatbot, Waterfall, Black Box Testing, Monitoring